Evaluation of Field Experience Practice Program (PPL) Students of FKIP Tribuana Kalabahi University - Alboin Selly (Peneliti.net, 2021)
This study aims to evaluate the expected field experience program (PPL) FKIP Tribuana Kalabahi University. become a consideration for the PPL program model that is in accordance with the potential and needs of education, and is also useful for perfecting the program system oriented to improving the quality of education, especially the competence of prospective educators This research is an evaluation research using the CIPP evaluation model. Respondents in this study were the Dean of FKIP, PPL Committee, PPL Students, Field Assistant Lecturers and Civil Service Teachers. Data were collected using questionnaires, interviews, observation and documentation studies. The data collected was then analyzed using a descriptive-qualitative method with a research design based on the CIPP evaluation model. The results of the evaluation show that the Field Experience Program (PPL) in general has met the success of the program, but there is also a need for improvement and refinement of several aspects that are evaluated.